JEJAK MAJAPAHIT: KOMPOSISI MUSIK PROGRAMA BERDASARKAN CERITA LEGENDA AIR MAJAPAHIT DI NEGERI EMA - Maitimu, Frengky; Lestari, Dewi Tika (Institut Seni Indonesia (ISI) Surakarta, 2023)
The history of Air Majapahit is one of the events of the arrival of Princess Majapahit in Negeri Ema which has been told orally from generation to generation. The history of Majapahit Water can be proven true by the existence of Majapahit kingdom relics in the form of heirloom spears, Gamelan, Betel places and Majapahit springs which are still well preserved in Negeri Ema. Based on this phenomenon, it was then used as a nonmusical concept to work on a musical composition. The composition of Traces of Majapahit is a narrative program musical work which contains elements of the history of Air Majapahit, which was created in the form of varied music and using western instruments. The process of creating the musical composition Traces of Majapahit went through several stages, namely (1) exploration of literature regarding musical disciplines and observation of Majapahit water history; (2) processing the relationship between musical elements and nonmusical concepts as a basis for the construction of musical compositions; (3) cultivating musical elements into variations using the main theme development procedure from Leon Stein’s theory; (4) presentation of the work in orchestra format. This work contains cultural value in the almost forgotten relationship between the Majapahit kingdom and Negeri Ema, so that through this work it is hoped that the history of Air Majapahit will be preserved.